New optical coherence tomography biomarker for diagnosis of acute optic neuritis in multiple sclerosis - Hend Mohammed Safwat; Sanaa Ahmed Mohamed; Ahmed Hassan Elsheshiny (Heliyon)
Objectives: Is imaging of retrolaminar optic nerve, during attack of acute optic neuritis in multiple sclerosis valuable? Methods: This is a prospective observational Case series study. Twenty two patients recruited from Al-Azhar University Hospitals and Charity Eye Centre (El-Mustafa Eye Centre, Cairo); from October 2022 to February 2024. The patients were referred; as, they had developed episode of acute optic neuritis. Full ophthalmic and neurological examinations were done for all patients within 2 weeks of acute optic neuritis. Imaging of peripapillary retinal nerve fiber layer by conventional spectral domain optical coherence tomography (OCT), and retrolaminar part of optic nerve by enhanced depth imaging OCT were done for both acute optic neuritis eyes and the fellow eyes. Results: A total of 44 eyes of 22 MS patients (18 females, 4 males) with the mean age of 30.54 ± 9.65 years were included in this study. The best corrected visual acuity (BCVA) was significantly less in the optic neuritis eyes (median = 0.30) than in the fellow eyes (median = 0.70), p = 0.007. Homogeneity of retrolaminar optic nerve tissue was altered in the optic neuritis eyes. OCT showed myelin aggregates as round or oval hyper-reflective foci in the optic neuritis eyes (95 % confidence interval: 2.90 [2.19–3.61]), that were not presented in the fellow eyes, p = 0.000. Conclusion: Using enhanced depth imaging OCT during acute attack of optic neuritis revealed retrolaminar hyper reflective foci as a new biomarker.